Combined Anatomical Variation of Axillary Artery and Biceps Brachii Muscle: A Case Report - Borthakur, Dibakar; Kaushal, Parul; S. B. Ray (Acta medica Lituanica, 2026)
Anatomical variations of the axillary artery and its branches are clinically relevant as they may complicate surgeries in the axilla and shoulder. Accessory heads of the biceps brachii can compress key neurovascular structures. The present report describes these variations observed on the left upper limb of a 79 years old male cadaver during cadaveric dissection. We observed that the usual branches of the 3rd part of the axillary artery as well as the profunda brachii artery originated from the 2nd part of the axillary artery via a common trunk in the left axilla. In addition to that, a small accessory head of the biceps brachii was observed on the left arm originating from the shaft of the humerus. Knowledge about variant branches of the axillary artery is surgically important for establishment of collateral circulation around the scapula following shoulder surgeries. The accessory head of biceps brachii may cause nerve entrapment neuropathy leading to mysterious pain syndrome in the upper limb.
Keywords: axillary artery; biceps brachii; third head of biceps